One-Stage Bilateral Total Hip Arthroplasty. Modern Representations and Our Experience - Kosiakov, O.M.; Bulych, P.V.; Hrebennikov, K.O.; Myloserdov, A.V.; Tuz, Ye. V.; Fedin, Ye.M.; Statkevych, M. V. (TERRA ORTHOPAEDICA, 2020)
Summary. Relevance. Total hip arthroplasty remains one of the most successful and cost-effective surgical interventions in modern medicine. This is proven by the ever-growing number of total arthroplasties worldwide, which reached 650,000 implantations in Europe only in 2018. In 2024, this number is expected to be 730,000 [1]. According to experts, from 15 to 25 percent of patients need a bilateral procedure [2, 8]. The experience of our Center allows us to recommend a successful one-stage replacement of both hip joints for patients with a number of medical and social comorbidities. Objective. The study is set out to highlight the possibilities of performing simultaneous bilateral arthroplasty of the hip joint in a group of patients with bilateral joint damage, as well as to substantiate the economic, medical and social benefits of this surgical intervention. Materials and Methods. We have analyzed the data from publications of our foreign colleagues. We also present our own observations – more than 100 cases over the past 11 years (2008-2019). Results. Based on data from foreign publications and our own observations, the undoubted advantages, features and limitations of this type of surgical intervention are shown. Complex cases of bilateral joint damage and the results of one-stage surgical treatment have been demonstrated. Conclusions. One-stage bilateral hip arthroplasty is the method of choice for symmetric lesions and should take its rightful place in the arsenal of modern orthopedics clinics. We continue to advocate simultaneous bilateral hip replacement for a selected group of healthy patients ≤65 years old. Thoughtful preoperative planning, surgical intervention lasting up to 90 minutes on each joint, careful postoperative monitoring, strictly controlled prevention of thromboembolic complications and active postoperative rehabilitation provide our patients with quick and safe functional recovery.